Parental education moderates the association between indoor moisture environment and asthma in adolescents: the Greek Global Asthma Network (GAN) cross-sectional study - George Antonogeorgos; Evangelia Liakou; Alexandra Koutsokera; Pavlos Drakontaeidis; Marina Thanasia; Maria Mandrapylia; Sotirios Fouzas; Philippa Ellwood; Luis García-Marcos; Demosthenes B. Panagiotakos; Kostas N. Priftis; Konstantinos Douros (BMC, 2022)
Abstract Objective Asthma is a major contributor to childhood morbidity. Several environmental and socioeconomic status (SES) factors have been implicated in its etiopathogeneses such as indoor moisture and parental education level. Our study examined the association between exposure to indoor dampness and/or mould (IDM) with adolescent asthma and how parental education could modify or mediate this relationship. Method A total of 1934 adolescents (boys: 47.5%, mean age (standard variation): 12.7(0.6) years) and their parents were voluntarily enrolled and completed a validated questionnaire on adolescents' asthma status, parental educational level, and adolescents' indoor exposure to IDM during three different lifetime periods, i.e., pregnancy, the first year of life and the current time. Results There was a significant modification effect of parental education only for the current exposure; higher parental education lowered almost 50% the odds of IDM and asthma (adjusted odds ratio (aOR): 1.96, 95% Confidence Intervals (CI): (1.05-3.68) and aOR:1.55, 95% CI (1.04-2.32), for primary/secondary and tertiary parental education, respectively). Conclusion Adolescents whose parents had a higher education level had lesser odds to have asthma, even if they were exposed to a moisture home environment. This could be attributed to the increased knowledge about asthma risk factors and the improved measures for the amelioration of moisture-home environment that highly educated parents are more likely to take. Further research is needed in order to elucidate the interweaved role of family SES in the aforementioned relation.